Multiple pathways carry signals from short‐wavelength‐sensitive ('blue') cones to the middle temporal area of the macaque. (21st November 2012) - Jayakumar, Jaikishan; Roy, Sujata; Dreher, Bogdan; Martin, Paul R.; Vidyasagar, Trichur R.
Key points:   The middle temporal area (area MT) of the macaque visual cortex receives visual signals from all three cone types, including short‐wavelength cones (S‐cones).   Signals from the short‐wavelength cones reach area MT both via the relay(s) in the primary visual cortex (V1) as well as a pathway bypassing V1.   The S‐cone signals to area MT that bypass V1 do not reach area MT significantly earlier than those that relay through V1.   The S‐cone signals that bypass V1 are most likely conveyed to area MT by direct projections from the koniocellular regions of the dorsal lateral geniculate nucleus.   Our results are consistent with the putative neuronal mechanism of the phenomenon of 'blindsight'. Abstract  We recorded spike activity of single neurones in the middle temporal visual cortical area (MT or V5) of anaesthetised macaque monkeys. We used flashing, stationary spatially circumscribed, cone‐isolating and luminance‐modulated stimuli of uniform fields to assess the effects of signals originating from the long‐, medium‐ or short‐ (S) wavelength‐sensitive cone classes. Nearly half (41/86) of the tested MT neurones responded reliably to S‐cone‐isolating stimuli. Response amplitude in the majority of the neurones tested further (19/28) was significantly reduced, though not always completely abolished, during reversible inactivation of visuotopically corresponding regions of the ipsilateral primary visual cortex (striate cortex, area V1). Thus, the present data indicate that signals originating in S‐cones reach area MT, either via V1 or via a pathway that does not go through area V1. We did not find a significant difference between the mean latencies of spike responses of MT neurones to signals that bypass V1 and those that do not; the considerable overlap we observed precludes the use of spike‐response latency as a criterion to define the routes through which the signals reach MT.